A porous precious metal catalyst and its preparation method and application

By preparing precious metal catalysts with porous structures, the problems of high amount of precious metals, high production costs and the need for added solvents and high pressure in the prior art are solved, and high efficiency dinitrotoluene hydrogenation reaction under low pressure and solvent-free conditions are achieved, which improves production efficiency and economic benefits.

CN115646485BActive Publication Date: 2025-04-04WANHUA CHEM GRP CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202211394039.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-08
Publication Date
2025-04-04
Estimated Expiration
2042-11-08

AI Technical Summary

Technical Problem

In the prior art, in the process of hydrogenation of dinitrotoluene, the use of precious metals is too high, the production cost is high, the need for additional organic solvents and high reaction pressure.

Method used

A noble metal catalyst with a porous structure is prepared by mixing precious metal salts, polymers, surfactants and solvents, and preparing them through spray drying, calcining and reduction to form a cage-type porous nanostructure catalyst. This method is simple in technology and is easy to produce on a large scale.

Benefits of technology

Under lower pressure and no added organic solvent, efficient conversion of dinitrotoluene was achieved, with DNT conversion rate ≥99.9%, TDA selectivity ≥98.8%, and tar product selectivity <0.5%, while reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115646485B_ABST
    Figure CN115646485B_ABST
Patent Text Reader

Abstract

The present invention provides a porous structured precious metal catalyst and a preparation method and application thereof, wherein the preparation method comprises the following steps: uniformly mixing a precious metal salt, a polymer, a surfactant and a solvent to obtain a mixed solution; spray drying, roasting and reducing the mixed solution in sequence to obtain the precious metal catalyst. The precious metal catalyst is a cage-type porous structure; the oxygen content of the precious metal catalyst is less than 500ppm, the carbon content is less than 5000ppm, and the remainder is precious metal; the pore size of the precious metal catalyst is 50-120nm. The precious metal catalyst is used for hydrogenating dinitrotoluene to prepare toluenediamine, and the reaction system does not need to add an organic solvent, which reduces side reactions and reduces production costs. At the same time, the reaction pressure is low, which can reduce equipment investment and improve economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogenation catalysts and preparation thereof, and in particular relates to a noble metal catalyst with a porous structure and a preparation method and application thereof. Background Art

[0002] Toluenediamine (TDA) is an intermediate in the preparation of toluene diisocyanate (TDI), and TDI is an important primary product in the preparation of polyurethane (PU). Polyurethane is widely used in elastomers, foam plastics, coatings, adhesives and fibers, and is one of the most promising synthetic materials.

[0003] At present, the main TDA synthesis processes include: iron powder reduction method, alkali sulfide reduction method, electrolytic reduction method, catalytic hydrogenation method, etc. The catalytic hydrogenation method has broad development prospects due to its advantages such as simple process, good product quality and low environmental pollution. The catalytic hydrogenation method is mainly divided into gas phase catalytic hydrogenation and liquid phase catalytic hydrogenation. Gas phase catalytic hydrogenation has a narrow application range due to the limitation of the boiling point of the raw materials; in contrast, liquid phase catalytic hydrogenation is valued by scientific researchers for its environmental friendliness, stable product quality and advanced process.

[0004] At present, liquid phase hydrogenation is widely used in industry to prepare TDA. The catalysts used in the liquid phase hydrogenation technology to prepare TDA process are mainly divided into two categories. One is a supported precious metal catalyst, which has the advantages of high hydrogenation activity, but the amount of precious metal used in supported precious metal catalysts is too high, resulting in expensive catalysts; the second is a Raney nickel-based catalyst, which has the advantages of low price and simple separation, but the activity of conventional Raney nickel-based catalysts is lower than that of precious metal catalysts, the reaction process requires an external solvent, and the reaction pressure is high and the equipment investment is large.

[0005] CN102744071A discloses a supported Urushihara nickel catalyst and a preparation method thereof, wherein the catalyst comprises: 1-20wt% Ni, 0.5-9wt% Fe, 0-30wt% of the Ni content in the auxiliary agent, and 65-98wt% in the carrier. The catalyst has good performance in the reaction of preparing toluenediamine by hydrogenation of dinitrotoluene, but after the catalyst is loaded, hydrochloric acid is required to extract the Fe used for replacement, which has an adverse effect on the Ni adsorbed on the surface of the carrier, and Ni is easily lost under stirring conditions, resulting in the deactivation of the catalyst; at the same time, the hydrochloric acid and soluble salt used in the preparation of the catalyst contain chloride ions, which cannot be completely removed in the later washing, have a negative impact on the catalyst, and the chloride ions are easy to cause corrosion of the device, limiting its application.

[0006] CN102580748A discloses an amorphous alloy catalyst for dinitrotoluene (DNT) hydrogenation and its application, wherein the catalyst comprises 5-30.0wt% Ni, 5-30.0wt% B, 0-5wt% additive, and SiO 2 The preparation method is: mixing a soluble metal salt solution with a water-soluble silicon source to prepare NiO / SiO 2 Precursor, then KBH 4 Solution reduction: The catalyst prepared by the method has good hydrogenation activity, but methanol or ethanol needs to be added as a solvent, and the gel formed is crushed and screened during the preparation of the precursor, and the silica gel below 300 mesh cannot be used, which increases the production cost; at the same time, the reducing agent reduces Ni 2+ The ion reaction takes place in the solution, causing part of the Ni to fall off, affecting the Ni content in the catalyst and further affecting the catalyst activity.

[0007] CN103977818A discloses a Raney nickel catalyst for low-pressure hydrogenation of dinitrotoluene, and its preparation method and application. The preparation method comprises the following steps: melting and atomizing nickel, aluminum and auxiliary metal to obtain alloy powder, alkali activation, and ultrasonic washing to obtain the catalyst. The prepared catalyst has good activity, but the required reaction pressure is high. In addition, the alloy powder needs to be screened, and the fine powder cannot be utilized, resulting in an increase in catalyst cost; NaOH is used during activation, which produces a large amount of alkali wastewater, and the cost of post-processing is high.

[0008] CN102274724A discloses a highly active catalyst for the hydrogenation reaction of aromatic nitro compounds and a preparation method thereof. The catalyst uses graphene as a carrier and Pt as an active component. The amount of Pt raw material used is relatively large, and the production cost is relatively high.

[0009] In summary, based on the defects existing in the above-mentioned prior art, it is necessary to provide a new catalyst for dinitrotoluene hydrogenation to avoid the use of excessive amounts of precious metal raw materials, reduce the production cost of the catalyst, and solve the problems of the need for additional organic solvents and excessive reaction pressure in the DNT hydrogenation reaction. Summary of the invention

[0010] The purpose of the present invention is to provide a porous structured precious metal catalyst and a preparation method and application thereof. The preparation method has a simple process and is easy to be industrialized on a large scale. The precious metal catalyst is used for preparing toluenediamine by hydrogenation of dinitrotoluene. The reaction system does not require an external organic solvent, thus reducing side reactions and production costs. At the same time, the reaction pressure is low, which can reduce equipment investment and improve economic benefits.

[0011] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0012] In a first aspect, the present invention provides a method for preparing a porous noble metal catalyst, the preparation method comprising the following steps:

[0013] (1) mixing the noble metal salt, the polymer, the surfactant and the solvent uniformly to obtain a mixed solution;

[0014] (2) The mixed solution in step (1) is spray-dried, calcined and reduced in sequence to obtain the noble metal catalyst.

[0015] The present invention first prepares a uniform solution of a noble metal salt, monodisperse polymer latex beads and a surfactant, and then prepares an inorganic-organic spherical mixture by spray drying, and then rapidly roasts the mixture in an air atmosphere to obtain a porous nano noble metal catalyst precursor with a cage structure, and then activates the mixture to obtain a finished catalyst product. The preparation method has a simple process and is easy to be mass-produced industrially.

[0016] As a preferred technical solution of the present invention, the precious metal salt in step (1) includes any one of palladium salt, platinum salt, iridium salt or ruthenium salt, or a combination of at least two of them. Typical but non-limiting examples of the combination include: a combination of palladium salt and platinum salt, a combination of platinum salt and iridium salt, or a combination of iridium salt and ruthenium salt, etc.

[0017] Preferably, the polymer in step (1) includes any one of PMMA (polymethyl methacrylate), ABS (acrylonitrile-butadiene-styrene copolymer), PAA (polystyrene), PEEK (polyetheretherketone) or PET (polyethylene terephthalate), or a combination of at least two of them.

[0018] In the present invention, the polymer is in the state of monodispersed latex beads.

[0019] Preferably, the particle size of the polymer in step (1) is 150 to 500 nm, for example, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0020] The present invention selects polymers with specific particle sizes so that they can be stably dispersed in a solution.

[0021] Preferably, the surfactant in step (1) comprises any one of coco-glucoside, lauryl glucoside, cetearyl glucoside, glyceryl monostearate or polysorbate, or a combination of at least two thereof. Typical but non-limiting examples of the combination include: a combination of coco-glucoside and lauryl glucoside, a combination of lauryl glucoside and cetearyl glucoside, a combination of glyceryl monostearate and polysorbate, and the like.

[0022] In the present invention, the solvent in step (1) includes deionized water.

[0023] In the present invention, the surfactant is a nonionic surfactant, which can stably disperse the polymer without agglomeration.

[0024] As a preferred technical solution of the present invention, the mass ratio of the noble metal salt and the solvent in step (1) is (0.02-0.1):1, for example, it can be 0.02:1, 0.04:1, 0.06:1, 0.08:1 or 0.1:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, the mass ratio of the polymer to the solvent in step (1) is (0.1-0.2):1, for example, it can be 0.1:1, 0.12:1, 0.14:1, 0.16:1, 0.18:1 or 0.2:1, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] Preferably, the mass ratio of the surfactant to the solvent in step (1) is (0.005-0.03):1, for example, it can be 0.005:1, 0.01:1, 0.015:1, 0.02:1, 0.025:1 or 0.03:1, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] As a preferred technical solution of the present invention, the spray drying in step (2) is: spray drying is performed using a spray drying device to obtain a spherical structure intermediate of the polymer-precious metal.

[0028] In the present invention, during the spray drying process, polymer latex beads self-assemble into droplets, and the noble metal material is coated around the polymer spheres to obtain a spherical structure with an inorganic noble metal salt or oxide on the outside and an organic polymer on the inside.

[0029] Preferably, the feeding rate of the mixed solution is 2 to 15 kg / h, for example, 2 kg / h, 4 kg / h, 6 kg / h, 8 kg / h, 10 kg / h, 12 kg / h or 15 kg / h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the inlet temperature of the drying air in the spray drying device is 300-450°C, for example, it can be 300°C, 330°C, 350°C, 370°C, 390°C, 400°C, 420°C, 440°C or 450°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the outlet temperature of the drying air in the spray drying device is 150-220°C, for example, it can be 150°C, 170°C, 190°C, 200°C, 210°C or 220°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the flow rate of the drying air in the spray drying device is 100-300 Nm 3 / h, for example, it can be 100Nm 3 / h、150Nm 3 / h、200Nm 3 / h、250Nm 3 / h or 300Nm 3 / h, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0033] In the present invention, the spray drying device includes a centrifugal spray dryer or a pressure spray dryer, the rotation speed of the centrifugal spray dryer is 5000-20000 rpm / min, and the pressure of the pressure spray dryer is 6-30 kg / cm 2 .

[0034] In the spray drying process of the present invention, the average diameter of the spherical structure intermediate particles can be controlled by changing the rotation speed of the centrifugal spray dryer, the pressure of the pressure spray dryer or other control parameters of the spray drying device and the concentration of the slurry.

[0035] As a preferred technical solution of the present invention, the calcination in step (2) is carried out in an air atmosphere.

[0036] Preferably, the heating rate of the calcination in step (2) is 20 to 50°C / min, for example, it can be 20°C / min, 25°C / min, 30°C / min, 35°C / min, 40°C / min or 50°C / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] In the present invention, the organic polymer inside the prepared spherical structure intermediate is decomposed and burned to generate gas by rapid heating in an air atmosphere, so that the precious metal forms a porous nanostructure. At the same time, the precious metal undergoes a self-reduction reaction during the calcination process, so that the structural stability of the catalyst is better.

[0038] Preferably, the temperature rise end point of the calcination in step (2) is 650-800°C, for example, it can be 650°C, 670°C, 700°C, 720°C, 740°C, 760°C, 780°C or 800°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0039] Preferably, the holding time for the calcination in step (2) is 4 to 8 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] Preferably, the reduction in step (2) comprises reduction in a hydrazine hydrate solution at 20 to 35°C or reduction in H2O2 at 180 to 220°C. 2 Reduction in atmosphere.

[0041] Preferably, the reduction time in step (2) is 1.5 to 3.0 h, for example, 1.5 h, 2.0 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3.0 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0042] In the present invention, the reduction treatment can fully reduce the noble metal active centers and further improve the catalyst activity.

[0043] In the present invention, the concentration of the hydrazine hydrate solution is 25-35%, for example, it can be 25%, 27%, 30%, 32% or 35%, etc., but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0044] In the present invention, the H 2 The concentration of the atmosphere is 15-25 v / v%, for example, it can be 15 v / v%, 17 v / v%, 20 v / v%, 22 v / v% or 25 v / v%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0046] (1) mixing a noble metal salt, a polymer, a surfactant and a solvent in a mass ratio of (0.02-0.1):(0.1-0.2):(0.005-0.03):1 to obtain a mixed solution;

[0047] (2) spray drying the mixed solution of step (1) at a feed rate of 2 to 15 kg / h using a spray drying device to obtain a spherical structure intermediate of a polymer-precious metal;

[0048] The inlet temperature of the drying air in the spray drying device is 300-450°C, the outlet temperature is 150-220°C and the flow rate is 100-300Nm 3 / h;

[0049] (3) heating the polymer-precious metal spherical intermediate in step (2) to 650-800° C. at a heating rate of 20-50° C. / min in an air atmosphere, and keeping the temperature for 4-8 hours to obtain a precious metal catalyst precursor;

[0050] (4) reducing the noble metal catalyst precursor in step (3) in a hydrazine hydrate solution at 20 to 35°C or in a hydrazine hydrate solution at 180 to 220°C. 2 The reduction is carried out in an atmosphere for 1.5 to 3.0 hours to obtain the noble metal catalyst.

[0051] In a second aspect, the present invention provides a precious metal catalyst with a porous structure, wherein the precious metal catalyst is prepared by the preparation method described in the first aspect.

[0052] The noble metal catalyst is a cage-like porous structure.

[0053] Preferably, the oxygen content of the noble metal catalyst is less than 500 ppm, the carbon content is less than 5000 ppm, and the balance is noble metal.

[0054] Preferably, the pore size of the precious metal catalyst is 50-120 nm, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm or 120 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] The noble metal catalyst of the present invention is a cage-like porous structure with a nanometer-level pore size, which is beneficial to the adsorption and diffusion of materials and improves the selectivity of the catalyst to the target product.

[0056] As a preferred technical solution of the present invention, the particle size of the precious metal catalyst is 1.0-5.0 μm, for example, it can be 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm or 5.0 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] Preferably, the specific surface area of ​​the noble metal catalyst is 20-40 m 2 / g, for example, 20m 2 / g, 24m 2 / g, 28m 2 / g, 30m 2 / g, 34m 2 / g, 38m 2 / g or 40m 2 / g, etc., but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] Preferably, the noble metal element in the noble metal catalyst includes any one of palladium, platinum, iridium or ruthenium, or a combination of at least two of them. Typical but non-limiting examples of the combination include: a combination of palladium and platinum, a combination of platinum and iridium, or a combination of iridium and ruthenium, etc.

[0059] In a third aspect, the present invention provides an application of the noble metal catalyst described in the second aspect, wherein the noble metal catalyst is used to catalyze the hydrogenation of nitro-containing compounds to prepare amino-containing compounds.

[0060] Preferably, the nitro-containing compound is dinitrotoluene, and the amino-containing compound is toluenediamine.

[0061] In a fourth aspect, the present invention provides a method for preparing toluenediamine, comprising: mixing the precious metal catalyst and solvent described in the second aspect into a hydrogenation reaction liquid, and then introducing hydrogen and dinitrotoluene to carry out a reduction reaction to obtain the toluenediamine.

[0062] Preferably, the solvent is deionized water.

[0063] Preferably, the mass ratio of the noble metal catalyst to dinitrotoluene is 1:(25-35), for example, 1:25, 1:27, 1:30, 1:32 or 1:35, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] Preferably, the reaction pressure is 0.8-1.2 MPa, for example, 0.8 MPa, 0.9 MPa, 1.0 MPa, 1.1 MPa or 1.2 MPa, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0065] Preferably, the reaction temperature is 100-120°C, for example, it can be 100°C, 104°C, 108°C, 110°C, 114°C, 118°C or 120°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] Preferably, the reaction time is 2 to 4 h, for example, 2 h, 2.4 h, 2.8 h, 3 h, 3.4 h, 3.8 h or 4 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0067] The noble metal catalyst prepared by the present invention can realize the efficient conversion of DNT under relatively low pressure and without organic solvent.

[0068] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0069] Compared with the prior art, the present invention has the following beneficial effects:

[0070] (1) Compared with supported noble metal catalysts, the porous nano-noble metal catalyst of the present invention has a cage-like porous structure, which is more conducive to the adsorption and diffusion of materials and can improve the selectivity of the catalyst for the target product;

[0071] (2) The preparation method of the present invention obtains an organic-inorganic mixed spherical intermediate by spray drying, and then the organic polymer inside is decomposed and burned to produce gas during the roasting process, so that the precious metal forms a porous nanostructure. At the same time, the precious metal undergoes a self-reduction reaction during the roasting process. The process flow is simple and easy to realize industrial large-scale production;

[0072] (3) The noble metal catalyst of the present invention is used for hydrogenating dinitrotoluene to prepare toluenediamine, and can achieve efficient conversion of DNT at a relatively low pressure and without the addition of an organic solvent, with a DNT conversion rate of ≥99.9%, a TDA selectivity of ≥98.8%, and a tar product selectivity of <0.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 This is a SEM image (2 μm) of the porous precious metal catalyst prepared in Example 1 of the present invention;

[0074] Figure 2 This is a SEM image (200 nm) of the porous precious metal catalyst prepared in Example 1 of the present invention;

[0075] Figure 3 This is the pore size distribution diagram of the porous precious metal catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0076] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0077] Example 1

[0078] This embodiment provides a porous noble metal catalyst and a preparation method thereof, the preparation method comprising the following steps:

[0079] (1) 30 g of palladium chloride, 100 g of monodisperse PMMA latex microspheres (average particle size 270 nm), 5 g of coconut glucoside and 1000 g of deionized water were mixed to obtain a mixed solution;

[0080] The PMMA latex microspheres are produced by Shanghai Zhenzhun Biological Company and are MSI-PM200NM and MSI-PM300NM.

[0081] (2) spray drying the mixed solution of step (1) at a feed rate of 2 kg / h using a pressure spray dryer to obtain a spherical structure intermediate of a polymer-precious metal;

[0082] The pressure of the pressure spray dryer is 20kg / cm 2 The inlet temperature of the dry air in the pressure spray dryer is 400-450°C, the outlet temperature is 180-220°C and the flow rate is 300Nm 3 / h;

[0083] (3) heating the polymer-precious metal spherical intermediate in step (2) to 650° C. at a heating rate of 30° C. / min in an air atmosphere, calcining the mixture, keeping the temperature for 4 h, and then cooling the mixture to room temperature to obtain a precious metal catalyst precursor;

[0084] (4) Place the noble metal catalyst precursor described in step (3) into a tubular reactor and introduce 20 v / v% H 2 The noble metal catalyst was obtained by reduction at 200° C. for 1.5 h.

[0085] The porous precious metal catalyst prepared in this example was subjected to SEM characterization and pore size distribution characterization, respectively, using a JSM-5900LV scanning electron microscope from JEOL and a PoreMaster 33 series mercury porosimeter from Anton Paar.

[0086] The SEM characterization results are as follows Figure 1-2 As shown in the figure, it can be seen that the noble metal catalyst has a cage-like porous nanostructure with a particle size of 1.0-5.0 μm.

[0087] The pore size distribution is characterized as follows: Figure 3 As shown, the pore size of the noble metal catalyst is 50-120nm and the specific surface area is 20-40m 2 / g.

[0088] The porous noble metal catalyst prepared in this example was subjected to elemental analysis using ICP-OES, the instrument model being 720ICP-OES produced by Agilent Technologies. After analysis, the oxygen content of the noble metal catalyst was less than 500ppm, the carbon content was less than 5000ppm, and the remainder was noble metal.

[0089] Example 2

[0090] This embodiment provides a porous noble metal catalyst and a preparation method thereof, the preparation method comprising the following steps:

[0091] (1) 50 g of iridium chloride, 200 g of monodisperse PEEK latex microspheres (average particle size 180 nm), 10 g of polysorbate and 1000 g of deionized water were mixed to obtain a mixed solution;

[0092] The grade of the PEEK latex microspheres is Victrex PEEK 450CA30;

[0093] (2) spray drying the mixed solution of step (1) at a feed rate of 2.0 kg / h using a pressure spray dryer to obtain a spherical structure intermediate of a polymer-precious metal;

[0094] The pressure of the pressure spray dryer is 25kg / cm 2 The inlet temperature of the dry air in the pressure spray dryer is 400-450°C, the outlet temperature is 180-220°C and the flow rate is 350Nm 3 / h;

[0095] (3) heating the polymer-precious metal spherical intermediate in step (2) to 800° C. at a heating rate of 50° C. / min in an air atmosphere, calcining the mixture, keeping the temperature for 4 h, and then cooling the mixture to room temperature to obtain a precious metal catalyst precursor;

[0096] (4) The noble metal catalyst precursor of step (3) is placed in a tubular reactor, 30% hydrazine hydrate solution is added and reduced at 25° C. for 1.0 h to obtain the noble metal catalyst.

[0097] Example 3

[0098] This embodiment provides a porous noble metal catalyst and a preparation method thereof, the preparation method comprising the following steps:

[0099] (1) 25 g of palladium chloride, 100 g of monodisperse PET latex microspheres (average particle size 200 nm), 10 g of glyceryl monostearate and 1000 g of deionized water were mixed to obtain a mixed solution;

[0100] The brand of the PET latex microspheres is DuPont PET 408NC010;

[0101] (2) spray drying the mixed solution of step (1) at a feed rate of 2.0 kg / h using a pressure spray dryer to obtain a spherical structure intermediate of a polymer-precious metal;

[0102] The pressure of the pressure spray dryer is 25kg / cm 2 The inlet temperature of the dry air in the pressure spray dryer is 400-450°C, the outlet temperature is 180-220°C and the flow rate is 350Nm 3 / h;

[0103] (3) heating the polymer-precious metal spherical intermediate in step (2) to 650° C. at a heating rate of 20° C. / min in an air atmosphere, calcining the mixture, keeping the temperature for 8 h, and then cooling the mixture to room temperature to obtain a precious metal catalyst precursor;

[0104] (4) Place the noble metal catalyst precursor described in step (3) into a tubular reactor and introduce 20 v / v% H 2 The noble metal catalyst is obtained by reduction at 200° C. for 0.5 h.

[0105] Example 4

[0106] This embodiment provides a porous noble metal catalyst and a preparation method thereof, the preparation method comprising the following steps:

[0107] (1) 30 g of palladium chloride, 100 g of monodisperse PAA latex microspheres (average particle size 200 nm), 10 g of glyceryl monostearate and 1000 g of deionized water were mixed to obtain a mixed solution;

[0108] The PAA latex microspheres are of the grade 3M PAA1162;

[0109] (2) spray drying the mixed solution of step (1) at a feed rate of 2.0 kg / h using a pressure spray dryer to obtain a spherical structure intermediate of a polymer-precious metal;

[0110] The pressure of the pressure spray dryer is 30kg / cm 2 The inlet temperature of the dry air in the pressure spray dryer is 400-450°C, the outlet temperature is 180-220°C and the flow rate is 350Nm 3 / h;

[0111] (3) heating the polymer-precious metal spherical intermediate in step (2) to 750° C. at a heating rate of 35° C. / min in an air atmosphere, calcining the mixture, keeping the temperature for 6 h, and then cooling the mixture to room temperature to obtain a precious metal catalyst precursor;

[0112] (4) Place the noble metal catalyst precursor described in step (3) into a tubular reactor and introduce 20 v / v% H 2 The noble metal catalyst is obtained by reduction at 200° C. for 0.5 h.

[0113] Example 5

[0114] This embodiment provides a porous structured precious metal catalyst and a preparation method thereof. Except that the amount of the monodisperse PMMA latex microspheres added in step (1) is 50 g, other conditions are the same as those in Example 1.

[0115] Example 6

[0116] This embodiment provides a porous structured precious metal catalyst and a preparation method thereof. Except that the amount of the monodisperse PMMA latex microspheres added in step (1) is 250 g, other conditions are the same as those in Example 1.

[0117] Example 7

[0118] This embodiment provides a porous structured precious metal catalyst and a preparation method thereof. Except that step (1) "30 g palladium chloride, 100 g monodisperse PMMA latex microspheres" is replaced by "50 g palladium chloride, 80 g monodisperse PMMA latex microspheres", other conditions are the same as those in Example 1.

[0119] Example 8

[0120] This embodiment provides a porous structured precious metal catalyst and a preparation method thereof. Except that step (1) "30 g palladium chloride, 100 g monodisperse PMMA latex microspheres" is replaced by "10 g palladium chloride, 120 g monodisperse PMMA latex microspheres", other conditions are the same as those in Example 1.

[0121] Example 9

[0122] This embodiment provides a porous structured precious metal catalyst and a preparation method thereof. Except that the heating rate of the calcination in step (3) is 10° C. / min, other conditions are the same as those in Example 1.

[0123] The porous structure of the precious metal catalyst prepared in this example was characterized by SEM and BET. The precious metal catalyst was a cage-like porous structure with a particle size of 3.0 μm. The pore size of the precious metal catalyst was 40.5 nm and the specific surface area was 25.0 m2 / g.

[0124] Example 10

[0125] This embodiment provides a porous structured precious metal catalyst and a preparation method thereof. Except that the heating end point of the calcination in step (3) is 550° C., other conditions are the same as those in Example 1.

[0126] Embodiment 11

[0127] This embodiment provides a porous structured precious metal catalyst and a preparation method thereof. Except that the heating end point of the calcination in step (3) is 900° C., other conditions are the same as those in embodiment 1.

[0128] Comparative Example 1

[0129] This comparative example provides a precious metal catalyst and a preparation method thereof. Except that the step (1) "100 g of monodisperse PMMA latex microspheres (average particle size 270 nm) and 5 g of coconut glucoside" are replaced by "200 g of silicon dioxide powder (particle size 200-500 nm)", the other conditions are the same as those in Example 1.

[0130] Comparative Example 2

[0131] This comparative example provides a noble metal catalyst and a preparation method thereof. Except that 5 g of coconut glucoside is not added in step (1), other conditions are the same as those in Example 1.

[0132] Comparative Example 3

[0133] This comparative example provides a noble metal catalyst and a preparation method thereof. Except that the spray drying in step (2) is adjusted to drying in an oven at 200° C., other conditions are the same as those in Example 1.

[0134] Comparative Example 4

[0135] This comparative example provides a noble metal catalyst and a preparation method thereof. Except that step (4) is not performed, other conditions are the same as those in Example 1.

[0136] Comparative Example 5

[0137] This comparative example uses 1.0 g of MC-507 commercial catalyst (purchased from EVONIK Company, brand: MC-507).

[0138] Comparative Example 6

[0139] This comparative example uses 1.0 g Pd / Al 2 O 3 Commercial catalyst (purchased from Xunkai, brand: PdCAT-3000Q).

[0140] Comparative Example 7

[0141] This comparative example uses 1.0 g of A-4000 commercial catalyst (purchased from Johnson Matthey Company, brand: A-4000).

[0142] Weigh 1 g of the catalyst prepared in the above embodiments and comparative examples respectively, add them to a high-pressure valve (500 mL) containing a stirring device, add 200 g of deionized water thereto, introduce hydrogen, the flow rate of hydrogen is 100 mL / min, the pressure of the high-pressure valve is maintained at 1.0 MPa, the oil bath temperature is 120°C, the rotation speed is 1500 r / min, weigh 30 g of DNT and heat to melt, use a high-temperature feed pump to add the molten DNT to the autoclave, the flow rate is 1 mL / min, after reacting for 3 hours, take a sample and analyze it by gas chromatography, the analysis results are shown in Table 1.

[0143] The gas chromatography analysis conditions used were: Agilent HP-INNOWAX column, injection port temperature: 280°C; detector temperature: 240°C; H 2 Flow rate: 35mL / min; Air flow rate: 350mL / min;

[0144] The calculation formula of DNT conversion rate is: DNT conversion rate = (1-DNT concentration in reaction solution) / (DNT concentration in raw material);

[0145] TDA selectivity calculation formula: TDA selectivity = product TDA concentration in the reaction solution / (concentration of other reaction products + TDA concentration).

[0146] Table 1

[0147] DNT conversion rate (%) TDA selectivity (%) Example 1 100 99.1 Example 2 100 99.2 Example 3 100 98.8 Example 4 100 99.0 Example 5 98.6 96.4 Example 6 95.2 97.6 Example 7 95.6 95.1 Example 8 93.8 95.6 Example 9 90.3 89.5 Example 10 92.7 94.8 Embodiment 11 96.2 91.7 Comparative Example 1 90.2 88.0 Comparative Example 2 86.5 90.9 Comparative Example 3 83.2 88.5 Comparative Example 4 98.7 98.2 Comparative Example 5 95.2 94.1 Comparative Example 6 99.6 96.2 Comparative Example 7 94.7 98.8

[0148] From Table 1, we can draw the following conclusions:

[0149] (1) The precious metal catalysts prepared by the preparation methods provided in Examples 1-4 of the present invention also have excellent catalytic DNT hydrogenation performance under relatively low pressure and without the addition of an organic solvent;

[0150] (2) It can be seen from Example 1 and Examples 5-6 that when the amount of polymer latex beads is too small, the droplets formed by the spontaneous combination of the polymer latex beads during spray drying are small, resulting in a small gas production during calcination, and the number of pores on the surface of the cage-like porous structure catalyst is small, resulting in reduced catalyst activity and a decrease in DNT conversion rate; when the amount of polymer latex beads is too large, the droplets formed by the combination of the latex beads are too large, the gas production during calcination is large, and the pore size of the formed part of the catalyst cage structure is too large or the cage structure is destroyed, resulting in reduced catalyst activity and a decrease in DNT conversion rate; It can be seen from Example 1 and Examples 7-8 that when the ratio of the precious metal salt and the polymer latex beads is not selected properly, the complete porous cage structure cannot be formed, resulting in reduced catalyst activity and a decrease in DNT conversion rate;

[0151] (3) Based on Example 1 and Examples 9-11, it can be seen that when the calcination heating rate is too low, the removal rate of the organic core is reduced, resulting in a smaller pore size and a smaller number of pores formed on the surface, which leads to a decrease in catalyst activity and a decrease in DNT conversion rate; when the calcination temperature is too low, the organic matter cannot be fully removed, resulting in a decrease in catalyst activity and a decrease in DNT conversion rate; when the calcination temperature is too high, the noble metal active center sinters, resulting in a decrease in catalyst activity and a decrease in DNT conversion rate;

[0152] (4) Based on Example 1 and Comparative Example 1, it can be seen that when the inorganic compound silica powder is mixed with the precious metal salt, a porous cage structure cannot be formed, resulting in poor catalyst activity and low DNT conversion rate. Based on Example 1 and Comparative Example 2, it can be seen that when no surfactant is added, the polymer is easy to agglomerate, resulting in poor catalyst activity and low DNT conversion rate.

[0153] (5) Based on Example 1 and Comparative Example 3, it can be seen that when the conventional drying method is used, the process of latex beads self-assembling into droplets cannot be achieved, resulting in poor catalyst activity and low DNT conversion rate;

[0154] (6) From Comparative Examples 5-7, it can be seen that the commercially available MC-507 catalyst has insufficient reaction activity, a low DNT conversion rate, and a large number of by-products are generated; the commercially available PdCAT-3000Q catalyst has high reaction activity, but generates a large number of by-products and has a low TDA selectivity; the commercially available A-4000 catalyst has insufficient reaction activity, a low DNT conversion rate, and generates a large number of by-products.

[0155] The applicant declares that the present invention illustrates the detailed structural features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An application of a porous precious metal catalyst, characterized in that: A noble metal catalyst and a solvent are mixed to form a hydrogenation reaction liquid, and then hydrogen gas is introduced to cause a reduction reaction with dinitrotoluene to obtain toluenediamine; The oxygen content of the noble metal catalyst is less than 500ppm, the carbon content is less than 5000ppm, and the balance is noble metal; the solvent is deionized water; the pressure of the hydrogen and dinitrotoluene reduction reaction is 0.8-1.2MPa; the particle size of the noble metal catalyst is 1.0-5.0μm, and the specific surface area of ​​the noble metal catalyst is 20-40m 2 / g, the pore size of the noble metal catalyst is 50-120nm; The noble metal catalyst is prepared by the following preparation method: (1) mixing the noble metal salt, the polymer, the surfactant and the solvent uniformly to obtain a mixed solution; The surfactant comprises any one of coconut glucoside, lauryl glucoside, cetearyl glucoside, glyceryl monostearate or polysorbate, or a combination of at least two thereof; the mass ratio of the surfactant to the solvent is (0.005-0.03):1; the mass ratio of the noble metal salt, the polymer and the solvent is (0.02-0.1):(0.1-0.2):1; (2) subjecting the mixed solution of step (1) to spray drying, calcination and reduction in sequence to obtain the noble metal catalyst; The spray drying comprises: using a spray drying device to perform spray drying to obtain a polymer-precious metal spherical structure intermediate; the feed rate of the mixed solution is 2-15 kg / h; the inlet temperature of the dry air in the spray drying device is 390-450° C., the outlet temperature is 150-220° C., and the flow rate is 100-300 Nm 3 / h; The heating rate of the calcination is 20-50°C / min; the heating end point of the calcination is 650-800°C.

2. The use according to claim 1, characterized in that: The noble metal salt in step (1) includes any one of palladium salt, platinum salt, iridium salt or ruthenium salt, or a combination of at least two of them.

3. The use according to claim 1, characterized in that: The polymer in step (1) includes any one of PMMA, ABS, PAA, PEEK or PET, or a combination of at least two of them.

4. The use according to claim 1, characterized in that: The particle size of the polymer in step (1) is 150 to 500 nm.

5. The use according to claim 1, characterized in that: The calcination in step (2) is carried out in an air atmosphere.

6. The use according to claim 1, characterized in that: The heat preservation time of the calcination in step (2) is 4 to 8 hours.

7. The use according to claim 1, characterized in that: The reduction in step (2) includes reduction in a hydrazine hydrate solution at 20-35°C or reduction in a H2 atmosphere at 180-220°C.

8. The use according to claim 1, characterized in that: The reduction time in step (2) is 1.5 to 3.0 hours.

9. The use according to claim 1, characterized in that: The method for preparing the noble metal catalyst comprises the following steps: (1) mixing a noble metal salt, a polymer, a surfactant and a solvent in a mass ratio of (0.02-0.1):(0.1-0.2):(0.005-0.03):1 to obtain a mixed solution; The surfactant includes any one of coconut glucoside, lauryl glucoside, cetearyl glucoside, glyceryl monostearate or polysorbate, or a combination of at least two thereof; (2) spray drying the mixed solution of step (1) at a feed rate of 2 to 15 kg / h using a spray drying device to obtain a spherical structure intermediate of a polymer-precious metal; The inlet temperature of the drying air in the spray drying device is 390-450°C, the outlet temperature is 150-220°C and the flow rate is 100-300Nm 3 / h; (3) heating the polymer-precious metal spherical intermediate in step (2) to 650-800° C. at a heating rate of 20-50° C. / min in an air atmosphere, and keeping the temperature for 4-8 hours to obtain a precious metal catalyst precursor; (4) reducing the precious metal catalyst precursor in step (3) in a hydrazine hydrate solution at 20 to 35° C. or in a H 2 atmosphere at 180 to 220° C. for 1.5 to 3.0 hours to obtain the precious metal catalyst.

10. The use according to claim 1, characterized in that: The noble metal catalyst is a cage-like porous structure.

11. The use according to claim 1, characterized in that: The noble metal element in the noble metal catalyst includes any one of palladium, platinum, iridium or ruthenium, or a combination of at least two of them.

12. The use according to claim 1, characterized in that: The mass ratio of the noble metal catalyst to dinitrotoluene is 1:(25-35).

13. The use according to claim 1, characterized in that: The temperature for introducing hydrogen and dinitrotoluene to undergo reduction reaction is 100-120°C.

14. The use according to claim 1, characterized in that: The time for introducing hydrogen and dinitrotoluene to undergo reduction reaction is 2 to 4 hours.

Citation Information

Patent Citations

  • A highly active catalyst for the hydrogenation reaction of aromatic nitro compounds and its preparation method

    CN102274724A

  • Amorphous alloy catalyst for hydrogenating dinitrotoluene and application of amorphous alloy catalyst

    CN102580748A

  • Supported urushibara nickel catalyst and preparation method thereof

    CN102744071A

  • Raney nickel catalyst used for low-pressure hydrogenation of dinitrotoluenem, preparation method and application thereof

    CN103977818A

  • Method for producing amines with a catalyst containing platinum, nickel and an additional metal

    CN101252987A